A deadly dance: the choreography of host–pathogen interactions, as revealed by single-cell technologies. Issue 1 (December 2018) - Chattopadhyay, Pratip; Roederer, Mario; Bolton, Diane
Abstract Pathogens have numerous mechanisms by which they replicate within a host, who in turn responds by developing innate and adaptive immune countermeasures to limit disease. The advent of high-content single-cell technologies has facilitated a greater understanding of the properties of host cells harboring infection, the host's pathogen-specific immune responses, and the mechanisms pathogens have evolved to escape host control. Here we review these advances and argue for greater inclusion of higher resolution single-cell technologies into approaches for defining immune evasion mechanisms by pathogens. Diane Bolton and colleagues review the impact of single-cell technologies on the study of host–pathogen interaction. They discuss the revolutionary impact these have had for facilitating a greater understanding of the properties of host cells harbouring infection, the pathogen-specific immune responses, and the mechanisms pathogens have evolved to escape host control.